A Constrative Study of Sociolinguistic Elements of Personal Pronouns of English and Vietnamese A Translational Perspective - Phạm Thị Như Tuyền (2007)
This study resulted from the researcher’s study of the translation into English of Vietnamese personal pronouns used in five short stories, “Chi Pheo”, “Old Hac”, “In the Moonlight”, “Buying a House”, “An Unworthy Life”, and the two novels ….